Meningkatkan Kepercayaan Diri Siswa Menggunakan Bimbingan Kelompok Dengan Teknik Sosiodrama Peserta Didik SMA N 4 Palangka Raya: Improving Self-Confidence Of Students Using Group Bimbing With Participants Of Sociodrama Techniques In Sma N 4 Palangka Raya - Esthi Puspitarini; Mohammad Fatchurahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to determine whether group counselling with sociodrama techniques could improve students' self-confidence. The research methodology used is the experiment. The population in this study was four palangkaraya public high school students. There is an increase in students 'self-confidence after the pre-test and post-test means